The Effect of Self-Efficacy and Rewards on Employee Performance: The Mediating Role of Organizational Citizenship Behavior - Afnan Abdulraheem Motea Alaqab; Alfato Yusnar Kharismasyah; Herni Justiana Astuti; Nawalin Nazah (Dinasti Review, 2026)
Employee performance is a critical determinant of organizational effectiveness, particularly in higher education institutions where non-academic staff play a vital supporting role. This study aims to examine the effect of self-efficacy and rewards on employee performance with organizational citizenship behavior (OCB) as a mediating variable among non-academic employees. This study employed a quantitative research approach with a total of 133 respondents from various divisions within the university. The data were analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM) version 4.1.6. The results indicate that self-efficacy has a positive and significant effect on employee performance, while rewards do not have a significant direct effect on employee performance. Self-efficacy and rewards both significantly influence organizational citizenship behavior. organizational citizenship behavior partially mediates the relationship between self-efficacy and employee performance and fully mediates the relationship between rewards and employee performance. These findings highlight the importance of psychological and behavioral mechanisms in enhancing employee performance within higher education institutions.